Sirt6 overexpression relieves ferroptosis and delays the progression of diabetic nephropathy via Nrf2/GPX4 pathway - Lingyu Du; Canghui Guo; Shengnan Zeng; Ke Yu; Maodong Liu; Ying Li (Renal Failure)
Objective Sirt6, reactive oxygen species and ferroptosis may participate in the pathogenesis of Diabetic Nephropathy (DN). Exploring the relationship between Sirt6, oxidative stress, and ferroptosis provides new scientific ideas to DN.Methods Human podocytes were stimulated with 30 mM glucose and 5.5 mM glucose. The mice of db/db group were randomly divided into two groups:12 weeks and 16 weeks. Collect mouse blood and urine specimens and renal cortices for investigations. HE, Masson, PAS and immunohistochemical staining were used to observe pathological changes. Western blot, RT-qPCR and immunofluorescence staining were used to evaluate expression of relevant molecules. CCK8 method was introduced to observe cell viability. The changes of podocyte mitochondrial membrane potential and mitochondrial morphology in each group were determined by JC-1 staining and Mito-Tracker.Results The expression level of Sirt6, Nrf2, SLC7A11, HO1, SOD2 and GPX4 were reduced, while ACSL4 was increased in DN. Blood glucose, BUN, Scr, TG, T-CHO and 24h urine protein were upregulated, while ALB was reduced in diabetic group. The treatment of Ferrostatin-1 significantly improved these changes, which proved ferroptosis was involved in the development of DN. Overexpression of Sirt6 might ameliorate the oxidation irritable reaction and ferroptosis. Sirt6 plasmid transfection increased mitochondrial membrane potential and protected morphology and structure of mitochondria. The application of Sirt6 siRNA could aggravated the damage manifestations.Conclusion High glucose stimulation could decrease the antioxidant capacity and increase formation of ROS and lipid peroxidation. Sirt6 might alleviate HG-induced mitochondrial dysfunction, podocyte injury and ferroptosis through regulating Nrf2/GPX4 pathway.